Method For Separation Of Platinum From PlatinumContaining Waste Solution - Orifjon Naziralievich Usmankulov (International Scientific and Current Research Conferences, 2021)
This article describes a new technology for the separation of platinum and palladium from solutions after gold electrolysis. As a result of the research, the presence of platinum metal in the solutions of the copper smelter of JSC “Almalyk MMC” was determined and work was carried out on its extraction. The concentration of platinum and palladium in the solution is low, so the method of forming an inelastic complex during their initial precipitation was used. This was followed by palladium and platinum refining steps involving several pyrometallurgical and hydrometallurgical processes. In the end, positive results were achieved and the developed new technology is applied to the production of these metals. [1]